EIF4G1 is a novel candidate gene associated with severe asthenozoospermia. Issue 8 (3rd July 2019) - Sha, Yanwei; Liu, Wensheng; Huang, Xianjing; Li, Yang; Ji, Zhiyong; Mei, Libin; Lin, Shaobin; Kong, Shuangbo; Lu, Jinhua; Kong, Lingyuan; Zhu, Xingshen; Lu, Zhongxian; et al.
Abstract: Background: Asthenozoospermia (AZS), also known as asthenospermia, is characterized by reduced motility of ejaculated spermatozoa and is detected in more than 40% of infertile patients. Because the proportion of progressive spermatozoa in severe AZS is <1%, severe AZS is an urgent challenge in reproductive medicine. Several genes have been reported to be relevant to severe asthenospermia. However, these gene mutations are found only in sporadic cases and can explain only a small fraction of severe AZS, so additional genetic pathogenies need to be explored. Methods and results: By screening the variant genes in a patient with severe AZS using whole exome sequencing, we identified biallelic mutations c.2521C>T: p.(Pro841Ser) (NC_000003.11: g.184043412C>T) in exon13 and c.2957C>G: p.(Ala986Gly) (NC_000003.11: g.184045117C>G) in exon17 in the eukaryotic translation initiation factor 4 gamma 1 gene ( EIF4G1, RefSeq: NM_004953.4, OMIM: 600495) of the patient. Both of the mutation sites are rare and potentially deleterious. Transmission electron microscopy analysis showed a disrupted axonemal structure with mitochondrial sheath defects. The EIF4G1 protein level was extremely low, and the mitochondrial marker cytochrome c oxidase subunit 4I1 (COXIV, OMIM: 123864) and mitochondrially encoded ATP synthase 6 (ATP6, OMIM: 516060) protein levels were also decreased in the patient's spermatozoa as revealed by WB and IF analysis. This infertility associated with this condition was overcome by intracytoplasmic sperm injections, as his wife became pregnant successfully. Conclusion: Our experimental findings indicate that the EIF4G1 gene is a novel candidate gene that may be relevant to severe AZS. Abstract : Sperm from patients with severe asthenozoospermia showed several morphology and ultrastructure defects in sperm flagella. We identified biallelic mutations of EIF4G1 gene. eIF4G1 protein was extremely low and the protein of COXIV and ATP6 was also decreased in mutant sperm. The patient successfully fertilized and raised baby by intracytoplasmic sperm injection.